The multidimensional nature of privacy risks: Conceptualisation, measurement and implications for digital services. (19th April 2022) - Karwatzki, Sabrina; Trenz, Manuel; Veit, Daniel
Abstract: While today consumers benefit from personalised service offerings, they are also understandably concerned about the privacy risks generated by disclosing their personal information online. We know that such perceived risks in general shape behaviour, but we know little about what specific privacy risks obstruct the use of digital services, making it difficult to implement technologies that could mitigate these risks. Based on qualitative and quantitative studies involving over 1000 participants, we conceptualise and quantify a multidimensional perspective on privacy risks consisting of physical, social, resource‐related, psychological, prosecution‐related, career‐related and freedom‐related privacy risks. Our results explicate the prospects of distinguishing privacy risk dimensions by demonstrating how they are differently pronounced across contexts and how technology designs can be tailored to assuage them. Thus, our findings improve the understanding of context and service‐specific privacy risks, helping managers to adjust their digital offerings to mitigate users' privacy risk perceptions.